Postmemorial Positions: Reading and Writing After the Holocaust in Anne Michaels’s Fugitive Pieces - Grimwood, Marita (Canadian Jewish Studies / Études juives canadiennes, 2003)
Anne Michaels’s novel, Fugitive Pieces, has been criticized forits highly poeticized representation of the Holocaust. In thisessay, however, Marita Grimwood argues that the novel usesstructures of narrative transmission to explore precisely thedifficulties of representing history and trauma in language.Grimwood proposes that the representation of three keycharacters is central to this undertaking. First, Jakob Beer, thechild survivor and poet who narrates two thirds of the novel, ispositioned as an intergenerational mediator, belonging fullyneither to a pre-war nor a postwar generation. Two further characters(Ben, the child of survivors who narrates the end of thenovel, and Michaela, Jakob’s second wife) symbolize the figureof the reader after the Holocaust, negotiating a link to the pastthrough their interpretation and witnessing of Jakob’s life.The novel recognizes the problems inherent in communicatingmeaningful knowledge of past events to those living inthe present. Yet, partly through Jakob’s vocation as a poet, it proposes also that poetry is a tool, however imperfect, for thecommunication of such knowledge.